Rifampicin-Induced Panic Disorder in a 70-Year-Old Woman With Brucellosis: A Case Report - Sunday Adeoye (BJPsych Open)
Aims: Panic disorder, also known as paroxysmal episodic anxiety, is a severe, unpredictable, and debilitating form of anxiety that is characterised by sudden onset of palpitations, chest pain, choking sensations, dizziness, and feelings of unreality (depersonalization or derealization). People that suffer from panic attack often have a secondary fear of dying or losing control. Like many other mental illnesses, the causes of panic disorder are unknown, but some predisposing factors have been identified including genetics, neurobiology, medications, psychiatric disorders, psychosocial factors and medical conditions.